Efficacy and Safety of 25% Trichloroacetic Acid Peel Versus 30% Salicylic Acid Peel in Mild-to-Moderate Acne Vulgaris: A Comparative Study - Dayal, Surabhi (Dermatol Pract Concept, 2021)
BACKGROUND: Both salicylic acid (SA) and trichloroacetic acid (TCA) have proven efficacy with good safety profiles in the treatment of acne vulgaris. OBJECTIVES: This study compared the clinical efficacy and safety of 25% TCA and 30% SA peels in the treatment of mild and moderate acne vulgaris. METHODS: Patients with mild or moderate acne vulgaris were randomized into 2 groups of 25 persons each, and treated with either the TCA peel or the SA peel at 2-week intervals for 12 weeks. Evaluation of active acne was done by individual lesion counts (comedones, papules and pustules) and calculation of the Michaelsson acne score (MAS). RESULTS: Both peels led to significant decrease in individual lesion counts and MAS compared to baseline values, without significant differences between the treatment groups. Thus, the peels had equivalent efficacy against acne vulgaris. The TCA peel was better in treating non-inflammatory lesions, while the SA peel was better for inflammatory lesions, but the differences were not significant. No serious adverse effects were recorded, but more patients in the TCA peel group experienced burning and stinging sensations. CONCLUSION: The efficacy of 25% TCA is comparable to that of 30% SA in mild-to-moderate acne vulgaris, but safety and tolerability were better with the SA peel than TCA peel.